Electron Spin Resonance Investigation of Hydrogen Absorption in Ball-Milled Graphite - Smith, C; Miyaoka, H; Ichikawa, T; Jones, M; Harmer, J; Ishida, W; Edwards, P; Kojima, Y; Fuji, H (2009)
Nanostructured hydrogenated graphite (CnanoHx) was synthesized here from graphite by ball-milling under a hydrogen (H2) atmosphere. X-ray diffraction (XRD), Fourier transform infrared (FT-IR), and transmission electron microscopy (TEM) show that ball milling results in the rupture of graphene sheets creating active defects and allowing hydrogen to be dissociated and then chemisorbed. Most likely small quantities of iron particles incorporated during the milling process act as a catalyst. C nanoHx thus possesses unique characteristic hydrogenated states present in nanometer scale particles, unlike standard hydride materials. Electron spin resonance (ESR) spectroscopy resolves two distinct paramagnetic components. The first is assigned to (intrinsic) delocalized π-electrons in the graphene sheets (g ~ 2.008) which disappears after approximately 32 h milling. The second ESR component grows in intensity with milling time and is assigned to localized electrons (g ~ 2.003) with a concentration of 3 × 1020 spins per gram after 80 h milling. HYSCORE spectroscopy reveals proton hyperfine couplings, and variable temperature CW ESR spectra demonstrate an unexpected magnetic ordering at low temperatures (~ 10 K). Formation of CnanoHx thus consists of weakly coupled localized electrons with wave functions that extends over small graphitic moieties. The radical centers do not physisorb a large quantity of H2 molecules under conditions required for practical H2 storage materials and are a product of the milling process and chemisorption of hydrogen. © 2009 American Chemical Society.